HUBUNGAN TANAH DASAR TERHADAP PERKERASAN LENTUR (FLEXIBLE PAVEMENT) JALAN RAYA - Simanjuntak, Johan Oberlyn; Saragi, Tiurma Elita; Simanjuntak, Salomo; Sipayung, Triwani (LPPM Universitas HKBP Nommensen, 2021)
The road is one of the important infrastructure in supportmobility of community activities. Based on the type of pavement can be dividedinto 3, namely flexible pavement, rigid pavement, and composite pavements. Construction problemsthe road is the subgrade and its compaction work. In this research leadsto the relationship of subgrade to flexible pavement. On flexible pavement there is a 3-layer structure, namely suface, base andsub-base. The thick structure of the flexible pavement layer is severely hampered by subgrade.In this Final Project, the analysis was carried out on 3 variations of CBR, namely 6%, 10%, and15% and compared to 2 variations of the material in the top foundation layer (LPA)and sub-base layer (LPB) and 2 variations of methods, namely the Bina Marga method andAASHTO. From the evaluation results with CBR variations, material variations and variationsmethod, obtained the results of the thickness of the pavement with CBR variations that are getting biggerCBR value, the smaller the thickness of the pavement layer, if seen from the variationthe material the lower the material quality, the thicker the pavement layer, and if it is seen from the variation of the method which is the most accurate and suitable to be appliedIndonesia is the DGH method. Then it can be denied that the subgrade andmaterial greatly affects the thickness of the flexible pavement layer.